Damage mechanics model for solder/intermetallics interface fracture process in solder joints - Shaffiar, Norhashimah; Laib, Z. B.; Tam, M. N. (Trans Tech Publications, Switzerland, 2011)
The relatively brittle solder/IMC interface fracture process in reflowed solder joints is examined using finite element (FE) method. The interface decohesion is described using a traction-separation quadratic failure criterion along with a mixed-mode displacement formulation for the interface fracture event. Reflowed Sn-4Ag-0.5Cu (SAC405) solder ball on OSP copper pad and orthotropic FR4 substrate under ball shear push test condition at 3000 mm/sec is simulated. Unified inelastic strain constitutive model describes the strain rate-response of the SAC405 solder. Comparable simulated and measured load-displacement values during solder ball shear push test serve as validation of the damage-based FE model. Results indicate a nonlinear damage evolution at each material point of the solder/IMC interface during the ball shear push test. The normal-to-shear traction ratio at the onset of the interface fracture is 1.59 indicating significant induced bending effect due to shear tool clearance. Rapid interface crack propagation is predicted following crack initiation event with the average crack speed up to 24.6 times the applied shear tool speed. The high stress concentration along the edge of the solder/IMC interface facilitates local crack initiation and dictates the shape of the predicted dynamic crack front.